2016
DOI: 10.12820/rbafs.v.21n2p172-180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional capacity and level of physical activity in adolescent and adult patients with cystic fibrosis

Abstract: The objective of the present study was to compare the functional capacity and level of physical activity between adolescent and adult patients with cystic fibrosis (CF) and healthy individuals. The six-minute walk test (6MWT) was used to evaluate functional capacity and the International Physical Activity Questionnaire (IPAQ - long version) was applied to assess physical activity level. This study included 31 patients with CF (11 males and 20 females) and 31 healthy individuals. Patients with CF had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(18 reference statements)
1
2
0
2
Order By: Relevance
“…We can observe with our results that FEV 1 was associated with MVPA, and the lower the FEV 1 , the lower the MVPA. Previous studies have come to our findings and show that adult CF patients practice PA at lower intensities when compared to healthy adults, with FEV 1 being a limiting factor for PA practice. Pastré et al found that the mechanisms responsible for limiting exercise in 102 adult CF patients with mild to moderate and severe disease were pulmonary function, nutritional status and inflammatory status …”
Section: Discussionsupporting
confidence: 69%
“…We can observe with our results that FEV 1 was associated with MVPA, and the lower the FEV 1 , the lower the MVPA. Previous studies have come to our findings and show that adult CF patients practice PA at lower intensities when compared to healthy adults, with FEV 1 being a limiting factor for PA practice. Pastré et al found that the mechanisms responsible for limiting exercise in 102 adult CF patients with mild to moderate and severe disease were pulmonary function, nutritional status and inflammatory status …”
Section: Discussionsupporting
confidence: 69%
“…In adults, one study reported significantly lower MET minutes per week (MET min·week −1 ) for the patient group (5307 versus 7808 MET min·week −1 ) (strength of conclusion: bias assessment level 3) [ 38 ]. In a mixed population, one study showed that significantly fewer patients were categorised in the highest tertile of PA based on the International Physical Activity Questionnaire (no patients with CF versus six healthy controls) (strength of conclusion: bias assessment level 3) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…MET hours per week (MET h•week −1 ). This was reported in five papers [28,32,35,37,38]. In youths, one study subjectively investigated total MET h•week −1 and reported significantly lower activity in CF compared to healthy peers (31.4 versus 52.0 MET h•week −1 ), whereas the remaining studies described no significant difference (strength of conclusion: bias assessment level 2) [28,32,35].…”
Section: Pa Of Pwcf Compared To Healthy Peersmentioning
confidence: 89%
“…En este estudio la mayoría de los participantes estaban en el nivel medio de educación. El resultado, teniendo en cuenta la proporción, es parecido a lo que ocurrió en España en el año 2011 donde la mayoría estaban cursando el nivel medio, esto se debe a los esfuerzos de los agentes implicados (familiahospital-asociaciones) en concienciar sobre la importancia de que estos adolescentes vivan como sus pares, realizando las mismas actividades y rutinas, de esa manera crecer con sentimientos de (20) mayor seguridad, confianza y autoestima , teniendo presente que el mejor nivel educativo proporciona (5) mayor posibilidad de conseguir empleo .…”
Section: Discussionunclassified
“…El dominio de estado emocional en este estudio tuvo el puntaje más alto, sin embargo otros estudios arrojaron puntajes bajos, estos generalmente (5,20) acompañan a la capacidad física . Se encontró una alta prevalencia de angustia psicológica incluyendo a los cuidadores, estos estudios en general son de m u e s t r a s p e q u e ñ a s , l o q u e d i f i c u l t a l a interpretación, pero en general la angustia psicológica va acompañada de poca adherencia al tratamiento, peor función pulmonar, frecuentes hospitalizaciones que disminuyen la calidad de (23) vida .…”
Section: Discussionunclassified